Applied Pedagogies for Higher Education Real World Learning and Innovation across the Curriculum - Morley, Dawn A.; Jamil, Md Golam (Springer Nature, 2021)
This open access book critiques real world learning across both the curriculum and extracurricular activities. Drawing on disciplines as diverse as business, health, fashion, sociology and geography, the editors and authors employ a cross-disciplinary approach to examine how this concept is being applied in higher education. Divided into three parts, the authors and contributors analyse broader applications of real world learning, student experience of practicing in a real world setting, and how learning strategies can be employed to engage students in real world learning. The editors and contributors provide up-to-date, cross-disciplinary and international insights into how real world learning could be integrated into the higher education curriculum to support effective, relevant and life-long learning for 21st century students.